Do the CAP Subsidies Increase Employment in Sweden? Estimating the Open Economy Relative Multiplier Using an Exogenous Change in the CAP - Johan Blomquist; Martin Nordin (Lund University, School of Economics and Management, Department of Economics, 2013)
This study evaluates the impact of agricultural subsidies (CAP) on unemployment and employment outside the agricultural sector. For the CAP subsidies to have an effect outside the agricultural sector, the subsidies must have a second-order effect. Thus, the Open Economy Relative Multiplier for Sweden is estimated with aggregate municipality data for the years 2001 to 2009. A side-effect of the decupling reform in 2005 was that Sweden was forced to introduce a grassland support which redistributed the payments among the regions. This exogenous redistribution of the CAP is the identifying assumption in this study. The subsidy creates private jobs at a cost of about 20,000 per job, which is consistent with earlier estimates based on US data.
Keywords: E24; E62; Q18; 330; Government Spending; Multiplier; Employment; Unemployment; CAP; Agricultural Subsidies